(untitled) (Economics and region, 2019)
The article defines the essence of the concept of "budget decentralization", reveals the main theoretical and legal aspects of the processes of budget decentralization, the peculiarities of reforming the administrative-territorial structure and the conditions for the formation of capable territorial communities. It is proved that the achievement of effective implementation of the budget decentralization reform is impossible without the formation of a financially viable grassroots administrative-territorial unit – the territorial community. The financial results of the activities of the united territorial communities of Ukraine, including: Poltava Region (Poltava Oblast) in 2015–2017 yrs. In the context of the united territorial communities of Poltava Region, the dynamics of income, expenditures and community surpluses / deficits were analyzed, incl. dynamics of income, expenditures per person in communities of Poltava region.